O-P08 Optimising design of national collaborative studies in surgery: national availability of electronic data in the NHS. (16th December 2021) - Thorne, Thomas; Hall, Lewis; McKay, Siobhan C; Wilkin, Richard W; Harvey, Phillip; Layton, Georgia; Roberts, Keith J; ,
Abstract: Background: Clinical trials are constrained in part by cost and limited funding opportunities. Trainee-led collaborative, multi-centre research models have become increasingly popular, enabling clinicians to undertake impactful national and international practice-changing studies with limited funding. However, ensuring equitable and efficient data collection from participating centres requires understanding data accessibility. Here, we reflect upon our strategies in designing and delivering collaborative research (The RICOCHET Study). Specifically, we consider the availability of data sources for UK hospitals, to enable effective design of study case report forms to ensure study success. Methods: RICOCHET was a National trainee-led audit of UK hospitals treating patients with pancreatic cancer. All registered hospitals were asked to complete a site-survey at point of registration. The site survey was completed by the lead consultant (surgeon or gastroenterologist) or the lead trainee at each site. The site-survey detailed hospital demographics, including size, availability of services and availability of patient data electronically. The survey was completed online via REDCap. Sites lacking full reporting were excluded from the analyses. Results: 98 UK sites registered for RICOCHET, and 94 completed the site-survey (26 specialist pancreatic sites; 68 non-specialist sites). 100% sites had electronic radiology reports. However, electronic ward-round notes were available at only 19% (5/26, 19.2% specialist vs. 13/68, 19.1% non-specialist; p = 0.99). Furthermore, sources such as external letters were low (29%; 11/26 42.3% specialist vs. 16/68, 23.5% non-specialist; p = 0.072). Although electronic interventional radiology reports were broadly available at 79% sites, this was significantly lower at non-specialist sites (49/68 72.1% vs. 25/26 96.2%; p = 0.011). Conclusions: Availability of electronic data is not consistent across sites managing pancreatic cancer patients. Significant disparity exists between specialist and non-specialist centres, highlighted by lack of availability of interventional radiology reports. To ensure success in trainee-led cohort studies we recommend designing concise case report forms that can be easily completed from electronic data sources. Until this report, there was no data available for the availability of electronic data across the NHS. This represents the most comprehensive report of such data sources, and will guide future study design of national studies at both specialist and non-specialist pancreatic centres in the UK.